2012
DOI: 10.1016/j.mambio.2012.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Free-ranging domestic cats reduce the effective protected area of a Polish national park

Abstract: a b s t r a c tPoland's Animal Protection Act, as of 2002, made it legal to shoot free-ranging cats and dogs. The act triggered substantial social debate with opponents arguing that this legislation was weakly supported by scientific evidence of the ecological impacts of free-ranging pets. Our main research goal was to examine the activity of free-ranging domestic cats within a Polish protected area by applying radio-telemetry methods to determine space use and degree of encroachment into the national park. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 60 publications
(84 reference statements)
1
20
0
1
Order By: Relevance
“…Urban and suburban cats mainly focus on birds, which results in serious predation rates (Lepczyk et al 2004) or increases in sub-lethal factors, such as a reduction in fecundity (Beckerman et al 2007) or food delivery to chicks (Bonnington et al 2013). Special attention should be paid to the influence of house cats on the fauna of nature reserves located in or adjacent to cities or suburbs as the presence of free-ranging domestic cats, which are likely the most abundant predator, can reduce the effectiveness of these protected areas as a tool for protecting nature (Wierzbowska et al 2012).…”
Section: Rural Urbanmentioning
confidence: 99%
See 1 more Smart Citation
“…Urban and suburban cats mainly focus on birds, which results in serious predation rates (Lepczyk et al 2004) or increases in sub-lethal factors, such as a reduction in fecundity (Beckerman et al 2007) or food delivery to chicks (Bonnington et al 2013). Special attention should be paid to the influence of house cats on the fauna of nature reserves located in or adjacent to cities or suburbs as the presence of free-ranging domestic cats, which are likely the most abundant predator, can reduce the effectiveness of these protected areas as a tool for protecting nature (Wierzbowska et al 2012).…”
Section: Rural Urbanmentioning
confidence: 99%
“…Consequently, even though food provisioning may reduce individual predation rates, the total impact of cat predation can be severe (reviewed in Baker et al 2005). Furthermore, free-ranging house cats hunt in both natural habitats as well as close to human settlements (Kays and DeWan 2004;Goszczyński et al 2008;Wierzbowska et al 2012), and the latter group are typically avoided by many wild carnivores because of the presence of humans (Krauze-Gryz et al 2012b). Finally, cats exhibit atypical hunting behaviour; i.e., they often kill and leave prey uneaten (Fitzgerald and Turner 2000;Krauze-Gryz et al 2012a;Loyd et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Home ranges of cats living on the edge of residential areas usually encompass neighbouring rural or forested habitat and these cats can have impacts on native wildlife (Gillies 2007;Lilith et al 2008;Tennent & Downs 2008;Metsers et al 2010Wierzbowska et al 2012). This can be of particular concern if the cats live close to areas of high conservation value such as national parks.…”
Section: Introductionmentioning
confidence: 99%
“…This can be of particular concern if the cats live close to areas of high conservation value such as national parks. Some studies have shown very limited movement of domestic cats into adjoining wild areas (Kays & DeWan 2004;Gillies 2007), whereas others have shown significant penetration by cats into wildlands (Metsers et al 2010;Wierzbowska et al 2012). In Poland, cats living in households within and surrounding a 2200-ha park potentially roamed throughout the entire park (Wierzbowska et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation